PENEGAKAN TINDAK PIDANA MAYANTARA (CYBERCRIME) DI POLRESTABES SEMARANG - Desta Rizki Priwidya, Nyoman Serikat Putra Jaya*), A.M. Endah Sri A (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Advances in technology have changed the structure of society that is local communities toward global structure. This change is caused by the presence of information technology. The development of information technology is combined with media and computers, which later gave birth to a new tool called the internet. The presence of internet has led to a new paradigm in human life. Life changed from being merely real (estate) to a new reality that is both virtual (virtual). The second reality is usually associated with the internet and cyber space. Issues to be raised in the writing of this law are:1.Knowing mayantara setting offense in law in Indonesia. 2.Knowing the types of crimes that occur in the region mayantara Polrestabes Semarang. 3.Knowing how the enforcement process is done by Polrestabes Semarang in practice so far. The research method used is empirical legal research. Research the law itself means that a process to find the rule of law to address the legal issues at hand. This research includes empirical legal research because this study uses data from the view of the authorities in Polrestabes Semarang, to obtain data related about mayantara crime (cybercrime) that occurred in Polrestabes Semarang.Number of reported cases of cybercrime were entered in the period from 2012 until May of 2013, cases were still under investigation by Polrestabes Semarang as many as 23 cases, 4 cases were terminated, 13 cases were transferred to the Central Java Police, and 2 cases that have been completed investigated by Polrestabes Semarang (file to the Public Prosecutor). The overall number of reported cases of cyber crime that goes on in 2012 until May 42 this is the case. Of the 42 cases that go most of the cases of cybercrime as criminal fraud, more than 50% of the total incoming cases as many as 24 cases. Based on data on the number of cyber crime cases reported in the period that goes from 2012 until May of 2013, cases were still under investigation by Polrestabes Semarang as many as 23 cases, 4 cases were terminated, 13 cases were transferred to the Central Java Police, and 2 cases that have been completed investigation by Polrestabes Semarang (file to the Public Prosecutor). From these data it can be concluded that the rule of law for criminal offenses mayantara still not up to it can be seen from 42 reports of criminal cases only 2 cases mayanrata file to the public prosecutor, it is due to the lack of human resources to handle criminal cases mayantara and yet there is legislation that specifically regulates mayantara crime.